Studien über Poljen in den venezianischen Voralpen und im Hochapennin - Lehmann, Herbert (ERDKUNDE, 1959)
The “piani in the Venetian Prealpes and the High Apennines have been exclusively formed by corrosive karst processes and a co-operation of tectonics - basining and faulting - cannot be proved. In fact the karst processes were preceded by phases of fluviatile planation or dissection, which, in turn, cut anterior tectonic structures, which had created zones of especial favour for the sub sequent karst processes. Such zones are especially the boundaries between two rocks of different liability to karstification, whereas the faultlines influenced more the preceding relief created by planation and dissection. The only thing possible, therefore, is to speak of a certain accordance of karst depressions to pre-existing tectonic structures, in the main due to differences in lithology. The karst depressions grow at the expense of the rocks more liable to karstification, also where their formation commences at fluviatilly modelled fault-lines. The karst depressions are not prior to the Middle Pliocene. It is not possible to comment in detail upon the nature of the preceding planation processes, the younger phases of which are still partly recognizable as marginal terraces in some depressions. They are likely to be of fluviatile origin, and developed near the baselevel of erosion. In the Apennines and the Venetian Prealpes these planation processes date back to the Pontien, without, however, having been capable of forming a peneplain. The formation of the karst depressions began with the nonuniform uplift of the old base-levelled flat relief and continued till the Early Pliocene. The Wurm glaciation found them already in their present shape. The melt water of glaciers ending in these depressions followed the drainage system of the karst, sometimes forming lakes. The non-glaciated depressions were partly filled up by soliflual material bringing about their flat bottoms and covering their slopes with mud tongues. The post-glacial processes modelling the poljes are: forming - respectively continued forming - of sink-holes, lowering of ponors connected to the incipient dissection of the polje-floor, erosion of the soliflual mantle and of the periglaeial alluvial cones, in the course of which the recent alluvial fans are formed. Terminologically speaking the karst depressions described here are poljes; this technical term, however, must no longer be made subject to the restriction that faulting was directly co-operating in their formation (A. Grund). Poljes are, in general, found in zones favourable to karstification (Structural accordance of karstmorphology), but a classification according to the geological structure as attempted by Cvijic does not seem useful. Based on physiognomic and morphogenetic points of view the present author proposes the following classification: I. Poljes on high erosion surfaces (“Hochflächenpoljen”) without preceding valley-systems a) poljes with flat bottoms (“ebensohlige Beckenpoljen) (Dinarian type) due to pleistocene accumulation, e. g. the polje of Castelluccio; b) poljes with numerous sink-holes (“Dolinenmuldenpoljen).They are honeycombed and have neither marked accumulation on the bottom nor apronounced knick between bottom and slope, e. g. the northern part of the polje of Bosco del Cansiglio. II. Valley poljes (“Talpoljen). The karst depression developed in a valley system. a) flat-bottomed poljes formed in aggraded valleys (“ebensohlige Aufschüttungstalpoljen); they have a marked knickline separating bottom and slope, e. g. Campo Felice, Piano di Pezza, Piano delle Ginque miglia; b) swale-shaped valley poljes (“muldenförmige Talpoljen) without marked boundary between bottom and slope, e. g. Piano Vuto, Piano Viano. III. Semi-poljes (“Semipoljen). Physiognomically and hydrographically they are real poljes which have, however, on one side impermeable rocks not liable to karstification a) complex semi-poljes (“komplexe Semipoljen), containing the non-calcareous rock within an extended complex of karstified limestone, e. g. the polje of Rocca di Cambio and Ovindoli, the polje of Quarto Grande and Quarto Chiara; b) marginal poljes (“Randpoljen), found on the boundary between rather extended non-karstifiable and karstified rock complexes; not found in the High Apennines, but on Cuba and Jamaica. The term Semipolje is somewhat insufficient and not identical with the term “Halbpolje, occasionally found in litterature, and also not identical with what is sometimes called fluviatilly “opened polje. The classification given here does not pretend to be of general applicability, but it seems appropriate to the poljes of the Apennine Peninsula.